MCL Plays an Anti-Inflammatory Role in Mycobacterium tuberculosis-Induced Immune Response by Inhibiting NF-κB and NLRP3 Inflammasome Activation - Qingwen Zhang; Xinru Jiang; Weigang He; Kailin Wei; Jinxia Sun; Xiangyang Qin; Yuejuan Zheng; Xin Jiang (Mediators of Inflammation)
Mycobacterium tuberculosis (Mtb) remains a significant menace to global health as it induces granulomatous lung lesions and systemic inflammatory responses during active tuberculosis (TB). Micheliolide (MCL), a sesquiterpene lactone, was recently reported to have a function of relieving LPS-induced inflammatory response, but the regulative role of MCL on the immunopathology of TB still remains unknown. In this experiment, we examined the inhibitory effect of MCL on Mtb-induced inflammatory response in mouse macrophage-like cell line Raw264.7 by downregulating the activation of nuclear factor kappa B (NF-κB) and NLRP3 inflammasome. Evidences showed that MCL decreased the secretion of Mtb-induced inflammatory cytokines (IL-1β and TNF-α) in a dose-dependent manner. Meanwhile, MCL dramatically suppressed Mtb-induced activation of iNOS and COX2 as well as subsequent production of NO. Furthermore, MCL inhibited Mtb-induced phosphorylation of Akt (Ser 473) in Raw264.7. According to our results, MCL plays an important role in modulating Mtb-induced inflammatory response through PI3K/Akt/NF-κB pathway and subsequently downregulating the activation of NLRP3 inflammasome. Therefore, MCL may represent as a potential drug candidate in the adjuvant treatment of TB by regulating host immune response.